The Journey Full of Emotions: Parents’ Experiences in Raising Children with Cerebral Palsy - Andromeda, Andromeda; Hartini, Nurul; Suryanto, Suryanto (Journal of ICSAR, 2023)
Raising a child with cerebral palsy (CP) is a formidable challenge for parents that can lead to tension and reality denial. This qualitative study aims to explore the parenting experience and the acceptance process of parents towards children with CP. This study used a qualitative design with semi-structured in-depth interviews. Three mothers and two fathers of children with CP were involved as interviewees. Data analysis was carried out using deductive thematic analysis technique. Common themes such as post-diagnosis denial; a long and emotional acceptance process; spouse's involvement in parenting; spiritual implication; the need for community support, are experienced by parents. Parental acceptance towards a child with CP is a long, complex, and emotional process. In conclusion, families that are able to achieve acceptance more easily adapting to family changes and dealing with stress. The findings of this study became an important milestone for the development of studies in the fields of family, disability, and social work.